Analysis of the teachers approaches in the development of oral communication skills with third year Baccalaureate students at Mariano Benitez Public School. - Chicaiza Chicaiza, Rosa María (2018)
This study examined teachers approaches to the development of oral communication skills with third-year baccalaureate students at Mariano Benitez public school. It also examines the impact of learner-centered teaching and learning process. Surveys validated by several authors were conducted with five teachers to find out the type of methodology they use. The opinions of third-year baccalaureate students were taken into consideration, who rated the teachers according to their methodology and the experiences they have had. Finally, direct observation was made by means of a checklist. The results show that the development of oral communication within the classroom could be improved in several aspects. Several activities are presented as a proposal that significantly contributes to the development of oral communication within the classroom occupying a methodology centered on the student and the teacher.